David versus Goliath: Airbnb and the New York Hotel Industry - McGowan, Richard; Mahon, John (Archives of Business Research, 2018)
The last half-decade has seen a sharp increase in both the number and popularity of peer-to-peer firms, which set up markets that allow individuals to borrow or sell under-utilized assets without a third-party intermediary. Firms that fall under this moniker – Uber, Lyft, DogVacay, and Airbnb – collectively make up what is often known as the “sharing economy” or “access economy;” their success can largely be attributed to easier access to technology by both suppliers and demanders, allowing markets to be seamlessly entered/exited and transactions to be mediated at low costs. Our research focuses on market segmentation between peer-to-peer firms and more traditional firms, looking specifically at New York City [NYC] Airbnb units and high end NYC hotels. According to their website, Airbnb is a “community marketplace for people to list, discover, and book unique accommodations around the world — online or from a mobile phone or tablet,” and has served over 60 millions guests in over 34,000 cities since its 2008 inception[1]. In short, Airbnb allows individuals to monetize extra space in their homes by leasing it out to travelers and other short-term renters[2]. While sharing economy firms in general have faced their share of backlash in many cities, Airbnb has encountered vehement opposition from the state government of New York [NY]. In October 2016, NY Governor Andrew Cuomo signed a bill that increased the maximum fine for short-term rentals in entire apartment buildings (Bensinger, 2016). Airbnb quickly filed a countersuit against the state, but settled soon after, agreeing to “crack down on individuals in New York City who rent out multiple homes, bowing to pressure from politicians and tenants’ rights groups who say the company has worsened affordable housing issues in the city” (Benner, 2016). The company has also suggested it would collect taxes on certain units, but politicians suggest that this would only legitimize the otherwise illegal business (Benner, 2016). As of February 2017, Airbnb has launched a campaign to track hotels and hotel representatives who have argued that Airbnb should contribute more through hotel taxes and then switched their position. The ongoing report claims that The Hotel Association of New York has indeed changed their position[3]. This research seeks to engage this debate by qualifying if NYC Airbnb units actually share a market with traditional hotels and, if so, how serious a player they are in that market. Our analysis finds that although Airbnb’s entry into the NYC short-term rental market has had a statistically significant effect on hotel revenue, occupancy, and average daily rate [ADR], but these effects are quite small.